THE ESSENCE OF TABOO AND SYMBOLS IN FAIRY TALES - Zebiniso Rasulova (Galaxy International Interdisciplinary Research Journal, 2025)
Taboos have a specific socio-moral essence. Because they are based on life experiences, they attract attention because they are tested by people's life experiences. They are performed by people to protect themselves from external negative influences, to guard against them. When performing the specified prohibitions, special symbolic actions are performed or objects considered magical are used. The article discusses taboos and magical objects in Uzbek folklore.